Cold Chain Business in Bangladesh to Enhance the Economic Growth of the Country - Hasan Maksud Chowdhury (International Journal of Supply Chain Management, 2012)
This descriptive study tries to find the economic and environmental impact on Bangladesh if cold chain technology of freezing shrimp is changed from conventional mechanical block process to liquid nitrogen individual quick frozen (LN IQF) process. The study also incorporates new business opportunity of cold chain and an effective supply chain of the frozen shrimp that would enhance the export of the country. The study was conducted based on the secondary data, i.e. analysis of the literature, journals, books and different publications of the stakeholders. It is found if the conventional mechanical process is changed to Liquid Nitrogen Individual Quick Frozen (LN IQF) process then, the country could earn extra 537 million per year and that could add to the GDP of the country. This LN IQF process could produce high quality frozen shrimp and would not create any harmful gases to the environment. Also there would be a new business opportunity of cold chain with a turnover of around 1004 million per year. Although the investment for the new business would be around 68 million, this investment cost of the LN IQF process could be recovered within two months from the extra earning of the frozen shrimps. The LN IQF would also allow the Bangladesh shrimp producers to access directly into the international shrimp market, since in the current process they have to go through the intermediate buyers to sell the frozen shrimps. This LN IQF would increase the effectiveness of the supply chain of the frozen shrimps from Bangladesh to the final consumers in the international market. KeywordsCold Chain, supply chain, Liquid Nitrogen (LN), Individual Quick Frozen (IQF), new business opportunity, economic and environmental impact.